Public and private choice in UK health insurance - John Hall; Ian Preston (Institute for Fiscal Studies (IFS), 1998)
Many parts of the public sector coexist with private provision of similar services and in such circumstances we may expect to find interaction between public and private choices. Quality of publicly provided services will be a central influence on decisions whether to make use of private substitutes and use of private substitutes will feed back into attitudes towards the level of public spending. In this paper we present evidence using the British Social Attitudes Survey to show that individual take up of private medical insurance inhibits support for spending on the public health sector. Such effects have been shown to be appreciable and allowance for the joint determination of insurance decisions and attitudes magnifies the size of the estimated effects.
Keywords: 330